1995
DOI: 10.1080/00927879508825509
|View full text |Cite
|
Sign up to set email alerts
|

Generating random elements of a finite group

Abstract: We present a "practical" algorithm to construct random elements of a finite group. We analyse its theoretical behaviour and prove that asymptotically it produces uniformly distributed tuples of elements. We discuss tests to assess its effectiveness and use these to decide when its results are acceptable for some matrix groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 10 publications
0
129
0
1
Order By: Relevance
“…(1 + t 2i−1 ) 4 /(1 − qt 2i ), which is    q 5 + 7q 4 + 25q 3 + 69q 2 + 146q + 172, n = 5, q 6 + 7q 5 + 25q 4 + 70q 3 + 171q 2 + 318q + 325, n = 6, q 7 + 7q 6 + 25q 5 + 70q 4 + 178q 3 + 387q 2 + 643q + 594, n = 7.…”
Section: Proposition 27 ([17])mentioning
confidence: 99%
See 1 more Smart Citation
“…(1 + t 2i−1 ) 4 /(1 − qt 2i ), which is    q 5 + 7q 4 + 25q 3 + 69q 2 + 146q + 172, n = 5, q 6 + 7q 5 + 25q 4 + 70q 3 + 171q 2 + 318q + 325, n = 6, q 7 + 7q 6 + 25q 5 + 70q 4 + 178q 3 + 387q 2 + 643q + 594, n = 7.…”
Section: Proposition 27 ([17])mentioning
confidence: 99%
“…This implies that every element of a large finite simple group is a product of two commutators. In [19] it is shown that the commutator map on finite simple groups is almost measure-preserving, a result having applications to the product replacement algorithm [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its maximal subgroups were constructed using the details supplied in [9] and the black-box algorithms of Wilson [20]. We also made extensive use of the algorithm described in [10] to construct random elements, and the procedures described in [3] and [4] The computations reported in this paper were carried out using Magma V.2.6-2 on a Sun UltraSPARC Enterprise 4000 server.…”
Section: The Modified Local Strategymentioning
confidence: 99%
“…We use the algorithm of [6] to generate random elements and in step 1 choose a sample of size 4d 2 .…”
Section: Implementation and Performancementioning
confidence: 99%
“…Another, more practical, option is the product replacement algorithm of Celler et al [6], which also runs in polynomial time (see [16]). For a discussion of both algorithms, we refer the reader to [18, pp.…”
Section: Introductionmentioning
confidence: 99%